2019
DOI: 10.1055/a-1012-7034
|View full text |Cite
|
Sign up to set email alerts
|

Rhein Augments Antiproliferative Effects of Atezolizumab Based on Breast Cancer (4T1) Regression

Abstract: Rhein, an anthraquinone extracted from rhubarb, is used in traditional Chinese medicine for diuresis, diarrhoea, inflammation, and immune regulation. Atezolizumab, a programmed cell death ligand 1 monoclonal antibody, is mainly used to treat bladder cancer and non-small cell lung cancer unresponsive to chemotherapy. We explored the effects of rhein and atezolizumab in combination on breast cancer. Mice with established 4T1 breast cancer xenografts were administered rhein (10 mg/kg) and atezolizumab (10 mg/kg),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Previous studies showed that IL6 and Tumor necrosis factor α (TNFα) could promote Tregs proliferation in tumor sites. The recent study reported that anti-PD-L1 treatment or the Rhein and combination therapy groups upregulated the IL6 level established 4T1 breast cancer xenografts [24]. Consistently, we also observed the slightly increase of IL6 in the tumor tissue after anti-PD-L1 therapy (data not show).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies showed that IL6 and Tumor necrosis factor α (TNFα) could promote Tregs proliferation in tumor sites. The recent study reported that anti-PD-L1 treatment or the Rhein and combination therapy groups upregulated the IL6 level established 4T1 breast cancer xenografts [24]. Consistently, we also observed the slightly increase of IL6 in the tumor tissue after anti-PD-L1 therapy (data not show).…”
Section: Discussionsupporting
confidence: 88%
“…This compound suppressed proliferation and inhibited breast cancer in mice. For instance, the administration of rhein has been shown to suppress tumor growth in 4T1-cell-induced mouse xenografts [146]. This study also showed that rhein in combination with atezolizumab synergistically elevated the expression of apoptotic protein such as Bax and caspases-3, -8, and -9, and decreased that of Bcl-2 [146].…”
Section: Breast Cancermentioning
confidence: 56%
“…For instance, the administration of rhein has been shown to suppress tumor growth in 4T1-cell-induced mouse xenografts [146]. This study also showed that rhein in combination with atezolizumab synergistically elevated the expression of apoptotic protein such as Bax and caspases-3, -8, and -9, and decreased that of Bcl-2 [146]. In another study, it was reported that rhein inhibited the phosphorylation of Akt and activated FOXO3a and further stimulated the activity of the pro-apoptotic protein Bim, which led to the cleavage of caspase proteins and subsequent induction of apoptosis in MCF-7 cells [144].…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, one study evaluated rhein's function in vivo. Rhein enhanced the apoptotic effect of atezolizumab on 4T1 BC cells (Shen et al, 2019). Treatment with a combination of rhein (10 mg/kg) and atezolizumab (10 mg/kg) inhibited 4T1 xenograft tumor growth and increased serum levels of tumor necrosis factor α and interleukin-6, the CD8 + T-cell ratio, apoptotic factors (e.g., caspase-3, caspase-8, and caspase-9), and Bax/Bcl-2 mRNA levels compared with rhein or atezolizumab treatment alone.…”
Section: The Role Of M 6 A-binding Protein In Breast Cancermentioning
confidence: 96%